Preparation method and application of perfluorocarbon nanoemulsion type hydrogen carrier

CN122669040APending Publication Date: 2026-09-01SUZHOU INST FOR ADVANCED STUDY USTC +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610789440.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-03
Publication Date
2026-09-01

AI Technical Summary

Technical Problem

然而,传统的PFC纳米乳液存在物理不稳定性问题,乳液中的颗粒在储存和使用过程中会因奥斯特瓦尔德熟化、胶束融合等动力学过程而发生粒径增大、分布变宽,不稳定的颗粒不仅会导致H2承载能力迅速衰减,更大的颗粒还可能包裹或吸附微生物细胞,阻碍其营养吸收和代谢活动,最终导致微生物电合成系统性能衰退

Benefits of technology

1、本发明采用全氟化碳纳米乳液作为氢气载体,利用其极高的气体溶解度特性,将水相中氢气的有效浓度大幅提高,从而显著增强氢气向微生物细胞的传质速率,相较于传统依赖溶解氢的体系,本载体系统能够持续、稳定地为产乙酸菌S.ovata提供充足的还原力,从根本上缓解了因氢气传质受限导致的反应速率下降问题,为高效微生物电合成提供了关键物质基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122669040A_ABST
    Figure CN122669040A_ABST
Patent Text Reader

Abstract

This invention relates to a method for preparing a perfluorinated carbon nanoemulsion hydrogen carrier and its application. (1) Polylactic acid-glycolic acid copolymer is dissolved in a solvent, perfluorinated carbon is added, and then a polyvinyl alcohol solution is added and mixed before ultrasonic treatment. The perfluorinated carbon includes perfluorohexane and perfluoronaphthane. (2) Polyvinyl alcohol solution is added to the ultrasonically treated solution in step (1) for homogenization, stirring, centrifugation, and washing to obtain nanoparticles. (3) The nanoparticles obtained in step (2) are dispersed in deionized water, and a surfactant is added and stirred to obtain the final product. The perfluorinated carbon nanoemulsion hydrogen carrier of this invention is used for efficient dissolution and transport of H2 to alleviate the limitation of H2 mass transfer, continuously provide reducing power for the microbial electrosynthesis process, and improve the yield, efficiency, and system stability of acetic acid without affecting the activity of microorganisms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of microbial electrochemistry, and in particular to a method for preparing a perfluorinated carbon nanoemulsion hydrogen carrier and its application. Background Technology

[0002] With the continued advancement of global industrialization, the energy crisis and climate change have become the most severe challenges facing humanity in the 21st century. Against this backdrop, electrochemical catalytic reduction technology, due to its mild reaction conditions and ability to be powered by renewable energy, is considered one of the important pathways for realizing the resource utilization of CO2. However, traditional inorganic electrocatalysts typically face problems such as low product selectivity, easy catalyst deactivation, and high energy consumption. In recent years, microbial electrosynthesis technology has emerged, ingeniously combining electrochemistry and biocatalysis. It utilizes microorganisms as highly efficient and specific biocatalysts, accepting electrons at the cathode to reduce CO2 into target chemicals, demonstrating enormous application potential.

[0003] Microbial electrosynthesis technology utilizes the complex enzyme systems inherent in microbial cells, such as carbon fixases and hydrogenases, as catalysts, and its advantages are obvious. First, because microbial metabolic pathways are specific, they can produce specific chemicals with high selectivity, such as acetic acid, ethanol, and methane, avoiding the problems of complex products and difficult separation and purification in traditional electrocatalysis. Second, microorganisms can self-replicate and have self-regeneration capabilities, theoretically enabling long-term stability. In addition, biocatalysis usually takes place near thermodynamic equilibrium potential, which helps to reduce energy consumption.

[0004] Perfluorocarbons (PFCs) are a class of inert organic compounds composed of carbon and fluorine atoms. Due to their unique physicochemical properties, PFCs have been extensively studied for many years in the biomedical field as artificial blood substitutes and ultrasound contrast agents, and they offer many advantages as gas carriers. However, traditional PFC nanoemulsions suffer from physical instability. During storage and use, the particles in the emulsion increase in size and widen in distribution due to kinetic processes such as Ostwald ripening and micellar fusion. Unstable particles not only lead to a rapid decline in H2 carrying capacity, but larger particles may also encapsulate or adsorb microbial cells, hindering their nutrient absorption and metabolic activities, ultimately causing a decline in the performance of the microbial electrosynthesis system.

[0005] Therefore, how to achieve efficient CO2 reduction through microbial electrochemistry has become an urgent technical problem to be solved. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a method for preparing a perfluorinated carbon nanoemulsion hydrogen carrier and its application. The perfluorinated carbon nanoemulsion hydrogen carrier prepared by this invention can be stable for 14 days, and...S.ovata Acetic acid accumulation of 39.2 mmol / L was achieved within fourteen days of co-cultivation.

[0007] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a perfluorinated carbon nanoemulsion hydrogen carrier, the method comprising: (1) dissolving polylactic acid-hydroxyacetic acid copolymer in a solvent, adding perfluorinated carbon, then adding a polyvinyl alcohol solution and mixing, followed by ultrasonic treatment; wherein the perfluorinated carbon includes perfluorohexane and perfluoronaphthane; (2) adding a polyvinyl alcohol solution to the solution after ultrasonic treatment in step (1) and stirring, centrifuging and washing to obtain nanoparticles; (3) dispersing the nanoparticles obtained in step (2) in deionized water, adding a surfactant and stirring to obtain the nanoparticles.

[0008] This invention proposes the construction of a composite nanocarrier with a core-shell-crown triple structure. PFC (perfluorocarbon) is encapsulated in a biodegradable polymer, polylactic-co-glycolic acid copolymer (PLGA), forming PFC@PLGA. PLGA provides rigid support for the PFC, effectively preventing leakage and fusion, and significantly enhancing the physical stability of the carrier. The outermost layer, formed by physical adsorption or chemical grafting of the amphiphilic surfactant Pluronic F68, is a hydrophilic and dynamic protective layer. This crown layer ensures good dispersibility and colloidal stability of the nanoparticles in the aqueous phase and provides a significant steric hindrance effect for the nanoparticle structure, preventing particle-particle collisions and fusion.

[0009] Preferably, in step (1), the ratio of the polylactic acid-glycolic acid copolymer to perfluorinated carbon is (10-15) mg: 100 μL. The (10-15) mg can be, for example, 10 mg, 11 mg, 12 mg, 13 mg, 14 mg, or 15 mg.

[0010] Preferably, in step (1), the volume ratio of perfluorohexane to perfluoronaphthalene is 1:(0.5-2). The (0.5-2) can be, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 2.

[0011] Preferably, in step (1), the solvent includes any one or a combination of at least two of dichloromethane, chloroform, ethyl acetate or acetone.

[0012] Preferably, in step (1), the amount of solvent added is 1-4 mL. The 1-4 mL can be, for example, 1 mL, 2 mL, 3 mL, or 4 mL.

[0013] Preferably, in step (1), the amount of polyvinyl alcohol solution added is 0.5-3 mL. The amounts may be 0.5 mL, 1 mL, 1.5 mL, 2 mL, 2.5 mL, or 3 mL, etc.

[0014] Preferably, in step (1), the concentration of the polyvinyl alcohol solution is 3-8%. The 3-8% can be, for example, 3%, 4%, 5%, 6%, 7% or 8%.

[0015] Preferably, in step (1), the ultrasonic treatment time is 3-8 minutes, and the ultrasonic treatment procedure is 1-5 seconds of ultrasonic treatment followed by 5-10 seconds of treatment. The 3-8 minutes can be, for example, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, or 8 minutes. The 1-5 seconds can be, for example, 1 second, 2 seconds, 3 seconds, 4 seconds, or 5 seconds. The 5-10 seconds can be, for example, 5 seconds, 6 seconds, 7 seconds, 8 seconds, 9 seconds, or 10 seconds.

[0016] Preferably, in step (2), the concentration of the polyvinyl alcohol solution is 3-8%. The 3-8% can be, for example, 3%, 4%, 5%, 6%, 7% or 8%.

[0017] Preferably, in step (2), the amount of polyvinyl alcohol solution added is 10-15 mL. The 10-15 mL can be, for example, 10 mL, 11 mL, 12 mL, 13 mL, 14 mL, or 15 mL.

[0018] Preferably, in step (2), the stirring time is 12-36 h. The 12-36 h can be, for example, 12 h, 18 h, 24 h, 30 h, or 36 h.

[0019] Preferably, in step (2), the centrifugation process is carried out at a temperature of 0-4℃, a centrifugation speed of 8000-12000 rpm, and a time of 5-15 min. The 0-4℃ can be, for example, 0℃, 1℃, 2℃, 3℃, or 4℃. The 8000-12000 rpm can be, for example, 8000 rpm, 9000 rpm, 10000 rpm, 11000 rpm, or 12000 rpm. The 5-15 min can be, for example, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, or 15 min.

[0020] Preferably, in step (3), the surfactant includes Pluronic F68.

[0021] Preferably, in step (3), the final concentration of the surfactant is 0.5-3%. The 0.5-3% can be, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, or 3%.

[0022] Preferably, in step (3), the stirring temperature is 0-4℃ and the stirring time is 12-36 h. The 0-4℃ can be, for example, 0℃, 1℃, 2℃, 3℃ or 4℃. The 12-36 h can be, for example, 12 h, 18 h, 24 h, 30 h or 36 h.

[0023] In a second aspect, the present invention provides a perfluorinated carbon nanoemulsion hydrogen carrier prepared according to the preparation method of the perfluorinated carbon nanoemulsion hydrogen carrier described in the first aspect.

[0024] Thirdly, the present invention provides a method for the electrochemical reduction of carbon dioxide based on microorganisms, the method comprising: […]. S.ovata After the bacterial culture is mixed with the perfluorinated carbon nanoemulsion hydrogen carrier described in the second aspect, microbial electrochemical culture is carried out.

[0025] The present invention adopts S.ovata The bacterial solution is Clostridium ovale ( Sporomusa ovata , S. ovata ).

[0026] Preferably, the method includes: (a) in constant potential mode, reduction is performed using a three-electrode electrochemical workstation, with the cathode chamber and anode chamber separated by an anion exchange membrane, and a mixed gas is introduced into the cathode chamber and a reducing solution is added for deoxygenation; (b) after deoxygenation in step (a), injection is performed into the cathode chamber. S.ovata The bacterial culture was carried out using a perfluorinated carbon nanoemulsion hydrogen carrier.

[0027] Preferably, in step (a), the mixed gas comprises 15-25% CO2 and 75-85% N2. The 15-25% can be, for example, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, or 25%. The 75-85% can be, for example, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, or 85%.

[0028] Preferably, in step (a), the aeration time of the mixed gas is 12-36 h, and the flow rate is 1-3 mL / min. The 12-36 h can be, for example, 12 h, 18 h, 24 h, 30 h, or 36 h. The 1-3 mL / min can be, for example, 1 mL / min, 1.5 mL / min, 2 mL / min, 2.5 mL / min, or 3 mL / min.

[0029] Preferably, in step (a), the reducing solution comprises 0.5-3 g / L sodium sulfide nonahydrate and 40-60 mM phosphate buffer. The 0.5-3 g / L can be, for example, 0.5 g / L, 1 g / L, 1.5 g / L, 2 g / L, 2.5 g / L, or 3 g / L, etc.

[0030] Preferably, in step (a), the amount of the reducing solution added is 0.1-1 mL. The 0.1-1 mL can be, for example, 0.1 mL, 0.2 mL, 0.3 mL, 0.4 mL, 0.5 mL, 0.6 mL, 0.7 mL, 0.8 mL, 0.9 mL, or 1 mL, etc.

[0031] Preferably, in step (a), the electrolyte added to the electrochemical workstation includes a buffer solution and a culture medium.

[0032] Preferably, in step (a), the buffer solution comprises 50-60 mmol / L phosphate buffer.

[0033] Preferably, in step (a), the culture medium comprises DSMZ 311 culture medium.

[0034] Preferably, in step (a), the counter electrode of the three-electrode system comprises a platinum mesh.

[0035] Preferably, in step (a), the reference electrode of the three-electrode system includes an Ag / AgCl electrode.

[0036] Preferably, in step (a), the working electrode of the three-electrode system comprises a silicon wafer.

[0037] Preferably, in step (a), the operating potential when the mixed gas is introduced is -0.5 to -0.3V. For example, it can be -0.5V, -0.45V, -0.4V, -0.35V, or -0.3V.

[0038] Preferably, in step (b), the S.ovataThe amount of bacterial solution added is 1-10 mL. The 1-10 mL can be, for example, 1 mL, 2 mL, 3 mL, 4 mL, 5 mL, 6 mL, 7 mL, 8 mL, 9 mL, or 10 mL, etc.

[0039] Preferably, in step (b), the S.ovata OD of bacterial culture 545nm The value is 0.3-0.8. The value of 0.3-0.8 can be, for example, 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8, etc.

[0040] Preferably, in step (b), the potential of the cathode chamber is -1.5V to -1.1V. For example, it can be -1.5V, -1.4V, -1.3V, -1.2V, or -1.1V, etc.

[0041] Preferably, in step (b), the amount of the perfluorinated carbon nanoemulsion hydrogen carrier added is 1-8 mL. The 1-8 mL can be, for example, 1 mL, 2 mL, 3 mL, 4 mL, 5 mL, 6 mL, 7 mL, or 8 mL.

[0042] Preferably, the method further includes hydrogen perfuming the perfluorinated carbon nanoemulsion hydrogen carrier before use.

[0043] Preferably, the hydrogen flow rate for the hydrogen treatment is 1-10 mL / min. The 1-10 mL / min can be, for example, 1 mL / min, 2 mL / min, 3 mL / min, 4 mL / min, 5 mL / min, 6 mL / min, 7 mL / min, 8 mL / min, 9 mL / min, or 10 mL / min, etc.

[0044] Preferably, the hydrogen perfusion treatment time is 3-5 minutes. The 3-5 minutes can be, for example, 3 minutes, 3.5 minutes, 4 minutes, 4.5 minutes, or 5 minutes.

[0045] Compared with the prior art, the present invention has at least the following beneficial effects: 1. This invention uses perfluorinated carbon nanoemulsion as a hydrogen carrier, taking advantage of its extremely high gas solubility to significantly increase the effective concentration of hydrogen in the aqueous phase, thereby significantly enhancing the mass transfer rate of hydrogen to microbial cells. Compared with traditional systems that rely on dissolved hydrogen, this carrier system can continuously and stably provide sufficient reducing power for acetic acid-producing bacteria S. ovata, fundamentally alleviating the problem of reaction rate decline caused by limited hydrogen mass transfer, and providing a key material basis for efficient microbial electrosynthesis.

[0046] 2. This invention constructs a PFC@PLGA-Pluronic F68 core-shell-crown triple structure, which improves the stability of the carrier while ensuring its good compatibility with the microbial system. The PLGA shell effectively prevents PFC leakage and fusion, while the Pluronic F68 crown provides steric hindrance, enabling the nanoemulsion to maintain uniform particle size and good dispersion under long-term storage and microbial culture conditions. Experiments show that this carrier can remain stable for at least 14 days at 30°C under continuous stirring conditions without inhibiting the growth and metabolism of *S. ovata*, which is significantly superior to traditional PFC emulsions.

[0047] 3. This invention can significantly improve the acetic acid yield and operational stability of the microbial electrosynthesis system. Under the same electrochemical culture conditions, the experimental group with this composite nanoemulsion achieved an acetic acid accumulation of 39.2 mmol / L within 14 days, significantly higher than the control group without the carrier. This carrier not only improves the product yield but also enhances the long-term operational stability of the system, avoiding the problem of decreased microbial activity caused by factors such as local pH increases and insufficient hydrogen supply. In addition, the carrier preparation process is mature, the raw materials are readily available, and it has good reproducibility and scale-up potential, providing reliable material support for the practical application of microbial electrosynthesis technology. Attached Figure Description

[0048] Figure 1 This is a schematic diagram of PFC@PLGA-Pluronic F68 composite nanoparticles.

[0049] Figure 2 Figure 1 shows the change in particle size of nanoemulsions with different perfluorinated carbon combinations over time. Figure 2a shows the result of the combination of PFTBA and PFH, Figure 3b shows the result of the combination of PFOB and PFH, and Figure 4c shows the result of the combination of PFD and PFH.

[0050] Figure 3 Figure 1 shows the change of PDI in nanoemulsions with different perfluorinated carbon combinations over time. Figure 2a shows the result of the combination of PFTBA and PFH, Figure 3b shows the result of the combination of PFOB and PFH, and Figure 4c shows the result of the combination of PFD and PFH.

[0051] Figure 4 Figure 1 shows the zeta potential of nanoemulsions with different perfluorinated carbon combinations over time. Figure 2a shows the result of the combination of PFTBA and PFH, Figure 3b shows the result of the combination of PFOB and PFH, and Figure 4c shows the result of the combination of PFD and PFH.

[0052] Figure 5The graph shows the changes in acetic acid concentration during the cultivation of S. ovata under different PFC nanoemulsion conditions. Group a is the detection result of the blank group, group b is the detection result of comparative example 1, group c is the detection result of comparative example 2, and group d is the detection result of example 1.

[0053] Figure 6 The graph shows the effect of different PLGA contents on the stability of PFC@PLGA-Pluronic F68 composite nanoemulsion. In the graph, a is the particle size variation graph and b is the PDI variation graph.

[0054] Figure 7 Figure 1 shows the effect of different Pluronic F68 contents on the stability of PFC@PLGA-Pluronic F68 composite nanoemulsion. Figure 2a shows the particle size variation, and Figure 3b shows the PDI variation.

[0055] Figure 8 The images show SEM images of PFC@PLGA-Pluronic F68 composite nanoparticles. Image a shows a local morphology of the particles at 20.0kx, image b shows the overall distribution of the particles at 3.0kx, image c shows the surface morphology of the particles at 6.0kx, and image d shows a high-magnification image of a single particle at 110kx.

[0056] Figure 9 The images show TEM images of PFC@PLGA-Pluronic F68 composite nanoparticles. Image a shows the overall distribution of the composite particles, image b shows a high-magnification image of a single particle, image c shows a local shell-like structure of the particles, and image d shows the characteristics of the particle boundaries and cavities.

[0057] Figure 10 The zeta potential distribution of the PFC@PLGA and PFC@PLGA-Pluronic F68 composite nanoemulsion is shown.

[0058] Figure 11 ATR-FTIR spectra of Pluronic F68, PFC@PLGA, and PFC@PLGA-Pluronic F68 composite nanoemulsions.

[0059] Figure 12 The figures show the storage stability characteristics of the PFC-Pluronic F68, PFC@PLGA, and PFC@PLGA-Pluronic F68 systems. Figure a shows the particle size variation, and Figure b shows the PDI variation.

[0060] Figure 13Figure 1 shows the system state changes of PFC-Pluronic F68, PFC@PLGA, and PFC@PLGA-Pluronic F68 during the electrochemical reaction process. Figure 2a shows the change in acetic acid concentration, and Figure 3b shows the change in Faraday efficiency. Detailed Implementation

[0061] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments. However, the following examples are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention is determined by the claims.

[0062] The sources of reagents used in the following examples are: PLGA: McLean Biotech Co., Ltd. Perfluorohexane: Maclean Biotech Co., Ltd.; Perfluoronaphthalene: Maclean Biotechnology Co., Ltd.; Pluronic F68: McLean Biotech Co., Ltd. Perfluorotributylamine: Maclean Biotechnology Co., Ltd.; Perfluorobromooctane: Maclean Biotech Co., Ltd.

[0063] Example 1 This embodiment utilizes microbial electrochemical reduction of carbon dioxide. 50 mg of PLGA was dissolved in 2 mL of dichloromethane. 200 μL each of perfluorohexane and perfluoronaphthane were added, followed by 1.26 mL of 5% PVA solution (w / v). After thorough mixing, the mixture was sonicated in an ice-water bath using an ultrasonic cell disruptor (Ningbo SCIENTZ-IID) for 5 min, with a program of 3 s on, 7 s off, and 600 W power output. After treatment, 12 mL of 5% PVA solution was added to homogenize the emulsion. The mixture was stirred openly at room temperature for 24 h to vaporize the organic solvent. The product was then centrifuged at 10,000 rpm for 10 min at 4 °C and washed with purified water to remove PVA.

[0064] The final product of PFC@PLGA nanoparticles was collected and dispersed in deionized water at 4℃. A 1.4% Pluronic F68 surfactant solution (w / v) was added to the solution, and the mixture was stirred at 4℃ for 24 hours to allow the surfactant Pluronic F68 to fully form a canopy on the PFC@PLGA nanoparticles, thereby obtaining a PFC@PLGA-Pluronic F68 composite nanoemulsion.

[0065] Before use, the PFC@PLGA-Pluronic F68 composite nanoemulsion was subjected to hydrogen purging at a flow rate of 5 mL / min for 4 min.

[0066] Electrochemical experiments were conducted in constant potential mode using a three-electrode system. An electrochemical workstation (Shanghai Chenhua, CHI660E) was used for control and measurement. The working electrode was a silicon wafer, the counter electrode was a 0.5 × 1.0 cm platinum mesh, and the reference electrode was an Ag / AgCl electrode. The anode and cathode chambers were separated by an anion exchange membrane (model FAA-3-PK-75). The electrolyte was DSMZ 311 inorganic salt medium prepared with 55.5 mM phosphate buffer. All potentials were referenced to Ag / AgCl (relative to the standard hydrogen electrode (SHE) of +0.209 V).

[0067] Before the experiment, a 20% CO2 / 80% N2 mixed gas was continuously introduced into the cathode chamber at a gas flow rate of 2 mL / min for 24 hours. The working potential was set to –0.4 V (vs. SHE), and 0.5 mL of reducing solution was added to completely remove residual oxygen. The reducing solution was 1 g / L sodium sulfide nonahydrate, and the solvent was 55.5 mM phosphate buffer. After deoxygenation, 5 mL of *S. ovata* bacterial culture (OD200) was injected into the cathode chamber containing 62 mL of electrolyte. 545 0.5 mL of nanoemulsion and 3 mL of S. ovata bacterial culture (OD200) were added simultaneously, while a setting was made by adding only S. ovata bacterial culture (OD200) 545 The control group (0.5) without nanoemulsion was used, and the cathode potential was adjusted to -1.3 V (vs. SHE) to start the microbial electrochemical culture. After that, electrolyte samples from the cathode and anode chambers were collected every 24 hours. The products were analyzed by nuclear magnetic resonance spectroscopy (1H NMR) and the changes in acetic acid production were monitored.

[0068] Example 2 This embodiment utilizes microbial electrochemical reduction of carbon dioxide. 40 mg of PLGA was dissolved in 1 mL of dichloromethane. 270 μL of perfluorohexane and 130 μL each of perfluoronaphthalene were added, followed by 0.5 mL of 8% PVA solution (w / v). After thorough mixing, the mixture was sonicated in an ice-water bath using an ultrasonic cell disruptor (Ningbo SCIENTZ-IID) for 3 min, with a program of 5 s on and 5 s off at 600 W power output. After treatment, 15 mL of 3% PVA solution was added to homogenize the emulsion. The mixture was stirred openly at room temperature for 12 h to vaporize the organic solvent. The product was then centrifuged at 8000 rpm for 15 min at 4 °C and washed with purified water to remove PVA.

[0069] The final product of PFC@PLGA nanoparticles was collected and dispersed in deionized water at 4℃. A 1.4% (w / v) solution of Pluronic F68 surfactant was added to the solution, and the mixture was stirred at 0℃ for 12 hours to allow the surfactant Pluronic F68 to fully form a canopy on the PFC@PLGA nanoparticles, thereby obtaining a PFC@PLGA-Pluronic F68 composite nanoemulsion.

[0070] The PFC@PLGA-Pluronic F68 composite nanoemulsion was subjected to hydrogen purging before use at a flow rate of 1 mL / min for 5 min.

[0071] Electrochemical experiments were conducted in constant potential mode using a three-electrode system. An electrochemical workstation (Shanghai Chenhua, CHI660E) was used for control and measurement. The working electrode was a silicon wafer, the counter electrode was a 0.5 × 1.0 cm platinum mesh, and the reference electrode was an Ag / AgCl electrode. The anode and cathode chambers were separated by an anion exchange membrane (model FAA-3-PK-75). The electrolyte was DSMZ 311 inorganic salt medium prepared with 55.5 mM phosphate buffer. All potentials were referenced to Ag / AgCl (relative to the standard hydrogen electrode (SHE) of +0.209 V).

[0072] Before the experiment, a 15% CO2 / 85% N2 mixed gas was continuously introduced into the cathode chamber at a gas flow rate of 3 mL / min for 12 hours. The working potential was set to –0.4 V (vs. SHE), and 0.1 mL of reducing solution (3 g / L sodium sulfide nonahydrate, 60 mM phosphate buffer) was added to completely remove residual oxygen. After deoxygenation, 1 mL of *S. ovata* bacterial culture (OD200) was injected into the cathode chamber containing 62 mL of electrolyte. 545 0.3 g of S. ovata bacterial culture (OD200) was added to 1 mL of nanoemulsion, and a separate setting was set where only S. ovata bacterial culture (OD200) was added. 545 The control group (0.3 V) without nanoemulsion was used, and the cathode potential was adjusted to -1.3 V (vs. SHE) to start the microbial electrochemical culture. After that, electrolyte samples from the cathode and anode chambers were collected every 24 hours. The products were analyzed by nuclear magnetic resonance spectroscopy (1H NMR) and the changes in acetic acid production were monitored.

[0073] Example 3 This embodiment utilizes microbial electrochemical reduction of carbon dioxide. 60 mg of PLGA was dissolved in 4 mL of dichloromethane. 130 μL of perfluorohexane and 270 μL each of perfluoronaphthalene were added, followed by 3 mL of 3% PVA solution (w / v). After thorough mixing, the mixture was sonicated in an ice-water bath using an ultrasonic cell disruptor (Ningbo SCIENTZ-IID) for 8 min, with a program of 1 s on and 10 s off, at 600 W power output. After treatment, 10 mL of 8% PVA solution was added to homogenize the emulsion. The mixture was stirred openly at room temperature for 36 h to vaporize the organic solvent. The product was then centrifuged at 12000 rpm for 15 min at 0 °C and washed with purified water to remove PVA.

[0074] The final product of PFC@PLGA nanoparticles was collected and dispersed in deionized water at 4℃. A 1.4% (w / v) solution of Pluronic F68 surfactant was added to the solution, and the mixture was stirred at 4℃ for 36 hours to allow the surfactant Pluronic F68 to fully form a canopy on the PFC@PLGA nanoparticles, thereby obtaining a PFC@PLGA-Pluronic F68 composite nanoemulsion.

[0075] The PFC@PLGA-Pluronic F68 composite nanoemulsion was subjected to hydrogen purging before use at a flow rate of 10 mL / min for 3 min.

[0076] Electrochemical experiments were conducted in constant potential mode using a three-electrode system. An electrochemical workstation (Shanghai Chenhua, CHI660E) was used for control and measurement. The working electrode was a silicon wafer, the counter electrode was a 0.5 × 1.0 cm platinum mesh, and the reference electrode was an Ag / AgCl electrode. The anode and cathode chambers were separated by an anion exchange membrane (model FAA-3-PK-75). The electrolyte was DSMZ 311 inorganic salt medium prepared with 55.5 mM phosphate buffer. All potentials were referenced to Ag / AgCl (relative to the standard hydrogen electrode (SHE) of +0.209 V).

[0077] Before the experiment, a 25% CO2 / 75% N2 mixed gas was continuously introduced into the cathode chamber at a gas flow rate of 1 mL / min for 36 hours. The working potential was set to –0.4 V (vs. SHE), and 1 mL of reducing solution (0.5 g / L sodium sulfide nonahydrate, 40 mM phosphate buffer) was added to completely remove residual oxygen. After deoxygenation, 10 mL of *S. ovata* bacterial culture (OD200) was injected into the cathode chamber containing 62 mL of electrolyte. 545 0.8 g of S. ovata bacterial culture (OD200) was added to 8 mL of nanoemulsion, while a setting was made by adding only S. ovata bacterial culture (OD200)545 The control group (0.8) without nanoemulsion was used, and the cathode potential was adjusted to -1.3 V (vs. SHE) to start the microbial electrochemical culture. After that, electrolyte samples from the cathode and anode chambers were collected every 24 hours. The products were analyzed by nuclear magnetic resonance spectroscopy (1H NMR) and the changes in acetic acid production were monitored.

[0078] Example 4 This embodiment describes the preparation of a PFC@PLGA-Pluronic F68 composite nanoemulsion hydrogen carrier. The only difference from Example 1 is that the amount of PLGA added is 25 mg and the amount of Pluronic F68 added is 5.6%. All other aspects are the same as in Example 1.

[0079] Example 5 This embodiment describes the preparation of a PFC@PLGA-Pluronic F68 composite nanoemulsion hydrogen carrier. The only difference from Example 1 is that the amount of PLGA added is 50 mg and the amount of Pluronic F68 added is 5.6%. All other aspects are the same as in Example 1.

[0080] Example 6 This embodiment describes the preparation of a PFC@PLGA-Pluronic F68 composite nanoemulsion hydrogen carrier. The only difference from Example 1 is that the amount of PLGA added is 100 mg and the amount of Pluronic F68 added is 5.6%. All other aspects are the same as in Example 1.

[0081] Example 7 This embodiment describes the preparation of a PFC@PLGA-Pluronic F68 composite nanoemulsion hydrogen carrier. The only difference from Example 1 is that the amount of PLGA added is 50 mg and the amount of Pluronic F68 added is 2.8%. All other aspects are the same as in Example 1.

[0082] Comparative Example 1 This embodiment describes the preparation of a PFC@PLGA-Pluronic F68 composite nanoemulsion hydrogen carrier. The only difference from Example 1 is that perfluorotributylamine (PFTBA) is used instead of perfluorohexane and perfluoronaphthane; otherwise, the embodiments are identical.

[0083] Comparative Example 2 This embodiment describes the preparation of a PFC@PLGA-Pluronic F68 composite nanoemulsion hydrogen carrier. The only difference from Example 1 is that perfluorobromooctane (PFOB) is used instead of perfluorohexane and perfluoronaphthane; otherwise, the embodiments are identical.

[0084] Test Example 1 This test case investigates the structure of the PFC@PLGA-Pluronic F68 composite nanoemulsion hydrogen carrier prepared in Example 1. The specific structure is as follows: Figure 1 As shown, this invention presents the basic composition and core-shell-crown triple structure of a perfluorinated carbon nanoemulsion hydrogen carrier. The composite nanoparticles, from the inside out, consist of a perfluorinated carbon core, a PLGA polymer shell, and a Pluronic F68 hydrophilic crown. The perfluorinated carbon core, mainly composed of perfluorohexane and perfluoronaphthane, is located inside the nanoparticles and serves as the primary region for hydrogen dissolution and storage. Because perfluorinated carbon has a high solubility for small molecule gases such as hydrogen, this core structure can increase the effective hydrogen carrying capacity of the system and provide a continuous source of reducing power for *S. ovata* during microbial electrochemical reactions. Encasing the perfluorinated carbon core is a polylactic acid-glycolic acid copolymer, i.e., the PLGA shell. This shell physically encapsulates the internal perfluorinated carbon, reducing leakage during storage or reaction, and inhibiting droplet fusion and Ostwald ripening, thereby improving the structural stability and long-term dispersion stability of the nanoemulsion. The outermost layer is a hydrophilic crown formed by Pluronic F68. Pluronic F68 is an amphiphilic nonionic surfactant whose hydrophobic segments interact with the PLGA shell, while the hydrophilic segments extend into the aqueous phase, forming a hydrophilic protective layer on the particle surface. This canopy enhances the dispersibility of particles in aqueous phases, electrolytes, and microbial culture systems, and reduces particle aggregation through steric hindrance. Simultaneously, Pluronic F68 exhibits good biocompatibility, helping to reduce the impact of nanoparticles on the growth and metabolic activity of *S. ovata* cells. Therefore, Figure 1 This invention visually demonstrates the design concept of a composite nanoemulsion hydrogen carrier: using perfluorinated carbon as the gas-carrying core, PLGA as a stable coating shell, and Pluronic F68 as a hydrophilic dispersion canopy, a composite nanoparticle with good hydrogen carrying capacity, colloidal stability, and microbial compatibility is constructed. This structure can improve hydrogen mass transfer efficiency during the electrochemical reduction of carbon dioxide by microorganisms, promoting the conversion of carbon dioxide to acetic acid by *S. ovata*.

[0085] Test Example 2 This test case explores the effects of Comparative Example 1 and Comparative Example 2. To investigate the effects of different perfluorinated carbon (PFC) combinations on the efficacy, this test case explored the effects of Example 1 and Comparative Examples 1-2. The stability of the composite nanoemulsion hydrogen carriers prepared above was investigated at 30°C and 300 rpm. Particle size, PDI, and Zeta potential were measured at 0, 24, 48, 72, 96, and 120 h to compare the dynamic stability behavior of different PFC systems under simulated culture conditions.

[0086] All three PFC nanoemulsions experienced varying degrees of instability during cultivation, mainly manifested as a continuous increase in droplet size, a gradual widening of particle size distribution, and a continuous decrease in the absolute value of surface potential. This indicates that the components of the culture medium, temperature, and oscillation collectively weakened the stabilizing effect of the emulsion interface layer, promoting droplet collisions and aggregation.

[0087] Particle size variation such as Figure 2 As shown, in terms of particle size changes, the PFTBA emulsion showed the most significant coarsening first under culture conditions, with its average particle size increasing from an initial 758.3±13.4 nm to 946.8±20.5 nm at 24 h, further increasing to 1184.1±24.6 nm after 48 h, and reaching 2108.7±37.3 nm at 120 h. This indicates that the PFTBA system is highly susceptible to droplet aggregation under culture medium and continuous shaking conditions, exhibiting the worst long-term dispersion stability. The PFOB emulsion particle size also increased continuously over time, from 585.6±13.4 nm to 1453.7±25.6 nm at 120 h. While its change was less pronounced than that of PFTBA, it still showed significant instability. In comparison, the PFD:PFH = 1:1 system had the smallest initial particle size of 169.4 ± 8.8 nm. Its growth was relatively slow in the early stages, but it gradually increased in size with prolonged culture time, reaching 1011.6 ± 26.6 nm at 96 h and 1318.4 ± 27.4 nm at 120 h. Although this system also struggled to maintain ideal nanoscale size during long-term culture, its particle size remained lower than the other two groups throughout the entire experimental period, indicating that its relative stability was still the best.

[0088] PDI changes as follows Figure 3As shown, the PDI of all three systems increased continuously with the extension of incubation time, indicating that the droplet size distribution gradually widened and the system homogeneity continuously decreased. The PDI of the PFTBA group increased from 0.291±0.012 to 0.643±0.019, showing the largest increase, indicating that the increase in droplet size was accompanied by more severe distribution deterioration. The PDI of the PFOB group increased from 0.221±0.011 to 0.525±0.016, showing a moderate degree of change. The PFD:PFH = 1:1 group had the lowest initial PDI, only 0.129±0.009, maintaining good dispersion homogeneity in the early stage, but also showing a significant increase in the later stage, reaching 0.514±0.018 at 120 h. Combined with the particle size results, it can be seen that although the PFD:PFH = 1:1 system is not completely stable during the incubation process, its instability process is relatively slow, and the overall system is still better than the PFTBA and PFOB groups.

[0089] From the changes in zeta potential, all three emulsions maintained a negative potential during cultivation, but their absolute values ​​gradually decreased. For example... Figure 4 As shown, the PFTBA group decreased from -14.1±0.8 mV to -5.8±0.4 mV, the PFOB group from -18.5±0.9 mV to -7.4±0.4 mV, and the PFD:PFH = 1:1 group from -24.1±1.2 mV to -9.1±0.6 mV. This change indicates that in the culture medium environment, the electrostatic repulsion of the droplet surface gradually weakens, the interfacial protection ability decreases, and thus the tendency for droplet aggregation is exacerbated. It is worth noting that the PFD:PFH = 1:1 system maintained a large absolute value of Zeta potential throughout the entire test period, which is consistent with its smaller particle size and lower PDI results, again indicating that its culture adaptability is better than the other two PFC systems.

[0090] The differences in stability among the three systems may be related to the physicochemical properties and interfacial behavior of different PFC cores. The PFTBA system exhibits a larger particle size and lower surface potential during the initial emulsification stage, indicating a relatively weak interfacial layer, making it more prone to instability under the influence of ionic strength and mechanical oscillation in the culture medium. The PFOB system shows improved stability but still cannot effectively suppress long-term aggregation. In contrast, the mixed core formed by combining PFD and PFH may have a better synergistic effect during droplet formation and interfacial rearrangement, resulting in superior overall stability in both initial preparation and subsequent culture stages.

[0091] Overall, under a culture medium environment of 30℃ and 300 rpm, all three PFC nanoemulsions exhibited varying degrees of instability over time, indicating that the simulated culture conditions pose a significant challenge to the stability of the emulsion interface. However, based on the relative comparison results, the PFD:PFH = 1:1 system showed the best performance in terms of particle size retention, dispersion uniformity, and surface potential, making it more suitable as a candidate hydrogen transfer carrier for subsequent hydrogen carrying capacity evaluation and microbial acetic acid production experiments.

[0092] Test Example 3 This test case investigates the changes in acetic acid concentration during the cultivation of *S. ovata* under different PFC nanoemulsion conditions. like Figure 5 As shown, comparing the blank group (the group containing only bacteria without any PFC) with Example 1, Comparative Example 1, and Comparative Example 2, the acetic acid concentration gradually increased over time, from approximately 2 mmol / L on day 1 to approximately 15 mmol / L on day 6. This indicates that the bacteria can complete the conversion of H2 / CO2 to acetic acid without PFC assistance, but the overall production is relatively limited. After adding PFTBA, the acetic acid concentration rapidly increased to approximately 17 mmol / L on day 2 and remained at approximately 17-18 mmol / L on days 3-6, indicating that PFTBA has a certain promoting effect on early acetic acid production, but the increase in the later stages is limited, and the system enters the plateau phase earlier. The acetic acid concentration in the PFOB group was generally higher than that in the PFTBA group, reaching approximately 18 mmol / L on day 2 and stabilizing at approximately 21-22 mmol / L after day 3, indicating that it has a stronger promoting effect on hydrogen transfer and acetic acid production. In contrast, the PFD:PFH = 1:1 group showed the best acetic acid production performance, with its acetic acid concentration increasing continuously in the first 4 days and further increasing to about 31 mmol / L on days 5-6, which was significantly higher than the other groups. This indicates that the PFC system can not only promote substrate utilization in the early stage, but also maintain a high level of acetic acid accumulation in the later stage.

[0093] The detection results of Examples 1, 2 and 3 are shown in Table 1.

[0094] Table 1 Acetic acid concentration (mM) Test Example 4 This test case explores the results of Examples 4-7. A comparison of Examples 4, 5, and 6 shows that, based on the particle size change results, as... Figure 6As shown, the particle size of the composite nanoemulsions prepared with three different PLGA contents gradually increased with time during the cultivation process, indicating that under the influence of continuous oscillation and the culture medium environment, the system underwent particle aggregation, interfacial rearrangement, or structural coarsening to varying degrees. However, the growth trends corresponding to different PLGA contents showed significant differences, indicating that the PLGA shell had a significant impact on the stability of the composite nanoemulsions.

[0095] A comparison of Examples 1, 5, and 7 shows that, as Figure 7 As shown, the particle size of all three composite nanoemulsions gradually increased with time during cultivation, indicating that under continuous cultivation and stirring conditions, the systems all underwent varying degrees of particle aggregation and structural coarsening. The particle size change trends of samples at different Pluronic F68 concentrations showed significant differences, suggesting that the surface canopy concentration plays a crucial regulatory role in the dispersion stability of the composite nanoemulsions.

[0096] Among the groups, the 1.4% PF68-50 mg PLGA group exhibited the smallest particle size increase throughout the entire culture period. The initial particle size of this group was approximately 190 nm, with relatively slow growth in the early stages, remaining below 750 nm after day 10, and increasing to approximately 1060 nm by day 14. In contrast, the 2.8% PF68-50 mg PLGA group showed a significantly faster particle size growth rate, with an initial particle size of approximately 200 nm, continuously increasing in the later stages of culture, reaching approximately 1080 nm by day 12. The 5.6% PF68-50 mg PLGA group showed the fastest particle size growth, with an initial particle size similar to the first two groups, but rapidly increasing after day 5, exceeding 1000 nm by day 10, significantly earlier than the other two groups. These results indicate that within the experimental range, increasing the concentration of Pluronic F68 did not synchronously improve the long-term stability of the composite nanoemulsion; excessively high concentrations of surfactant actually exacerbated particle size growth.

[0097] Test Example 5 This test case explores the physical properties of Example 1. Figure 8 SEM image of PFC@PLGA-Pluronic F68 composite nanoemulsion hydrogen carrier, as shown. Figure 8As shown in Figures a and b, the sample exhibits a relatively dispersed granular structure on the substrate surface after drying, with an overall spherical or near-spherical morphology, indicating that the prepared composite nanoemulsion can form relatively independent particle units. There are certain size differences between the particles; in some areas, smaller particles are distributed around larger particles, suggesting that the sample retains some particle dispersion characteristics in the dried state, but also exhibits a certain degree of inhomogeneity. This phenomenon is basically consistent with the particle size distribution characteristics reflected in the dynamic light scattering results, indicating that the composite nanoemulsion obtained a relatively stable particle structure during the formation process.

[0098] pass Figure 8 As shown in Figure c, some particles exhibit obvious wrinkles, depressions, or shell collapse on their surfaces, with some larger particles displaying irregular elliptical or vesicular structures. This phenomenon indicates that after the sample underwent dehydration and a vacuum environment during SEM preparation, the nanoemulsion particles, which were originally in a hydrated state, may have experienced volume shrinkage and surface morphology rearrangement. For composite nanoemulsions containing volatile perfluorinated carbon cores, core dissipation and PLGA shell shrinkage during drying can both lead to localized collapse and surface wrinkles in the particles. Therefore, the morphology observed in the figure better reflects the residual structural characteristics of the particles under solid-state drying conditions, rather than the original morphology of the particles in aqueous solution. Figure 8 Image d is a high-magnification image, showing relatively clear boundaries between individual particles and particle sizes ranging from submicron to nanometer, indicating that the obtained sample possesses nanoscale structural characteristics. Combining low-magnification and high-magnification images reveals that the PFC@PLGA-Pluronic F68 composite nanoemulsion retains some particle outlines after drying, but the particle morphology is not completely regular and smooth, exhibiting varying degrees of deformation and collapse. This result is related to the core-shell structure characteristics of the composite nanoemulsion itself, and may also be influenced by factors such as sample dehydration, substrate adsorption, and gold sputtering treatment.

[0099] Figure 9 The TEM image shows the PFC@PLGA-Pluronic F68 composite nanoemulsion hydrogen carrier. Individual particles exhibit clear annular boundaries with relatively regular outer contours. The difference in electron density between the central and peripheral regions indicates a core-shell structure. This result suggests that the sample is not a uniform solid particle, but rather a composite structure with PFC as the core, PLGA as the main coating layer, and an outer hydrophilic canopy of Pluronic F68 adsorbed or constructed. Due to the differences in the transmittance and staining response of the different components under electron beam, a distinct layered contrast of light and dark is observed in the TEM image.

[0100] like Figure 10As shown, the peak position of the Zeta potential distribution of the PFC@PLGA nanoemulsion without Pluronic F68 modification is around -36.01 mV, while the peak position of the Zeta potential of the PFC@PLGA-Pluronic F68 composite nanoemulsion modified with Pluronic F68 shifts significantly in the positive direction, to around -15.80 mV. Both exhibit negative charge, indicating that when PLGA is used as an outer coating material, the particle surface carries a certain negative charge. After the introduction of Pluronic F68, the absolute value of the particle surface potential decreases significantly, indicating that Pluronic F68 has been successfully adsorbed or assembled on the particle surface and has a significant impact on the original surface charge distribution.

[0101] The PFC@PLGA sample exhibits a high absolute value of negative Zeta potential, indicating strong electrostatic repulsion between its particles, which plays a positive role in maintaining the dispersion stability of the colloidal system. In contrast, the surface potential of PFC@PLGA-PluronicF68 shifts towards lower absolute values, suggesting that the introduction of Pluronic F68 reduces the exposure of negative charges on the particle surface. This may be because the hydrophilic segments in the Pluronic F68 molecule cover the particle surface, shielding the charged groups on the PLGA surface to some extent, causing the particle interface to gradually shift from being primarily electrostatically stable to being primarily stable by the steric hindrance provided by the hydrophilic segments.

[0102] To further verify the composition and interfacial modification of the PFC@PLGA-Pluronic F68 composite nanoemulsion, ATR-FTIR characterization was performed on Pluronic F68, PFC@PLGA, and PFC@PLGA-Pluronic F68 samples. Figure 11 As shown.

[0103] Test Example 6 This test case is used to investigate stability. This study compared the changes in particle size and PDI of three groups of samples during storage: PFC-Pluronic F68, PFC@PLGA (without Pluronic F68 modification), and PFC@PLGA-Pluronic F68. The results are as follows: Figure 12 As shown. By Figure 12As shown in Figure a, the particle size of all three groups of samples increased with storage time, but the growth rate and magnitude of change differed significantly. The PFC group showed the fastest particle size growth, increasing rapidly from approximately 150 nm initially to approximately 880 nm by day 5, indicating that the free perfluorocarbon system is highly susceptible to droplet coalescence and particle aggregation during storage, resulting in poor system stability. The PFC@PLGA group had a slightly higher initial particle size than the PFC group, but its particle size also increased rapidly in the early stages, reaching approximately 1190 nm by day 6. This suggests that while PLGA coating can improve the dispersion of PFC to some extent, it is insufficient to effectively suppress particle aggregation and size increase during storage. In contrast, the PFC@PLGA-Pluronic F68 group exhibited a slower particle size growth trend throughout the observation period, increasing from approximately 180 nm initially to approximately 930 nm by day 12, and maintaining a particle size below 400 nm for the first 6 days, significantly better than the PFC and PFC@PLGA groups. This indicates that the storage stability of the composite nanoemulsion was significantly improved after further introducing Pluronic F68 on the basis of PLGA coating.

[0104] From the particle size variation pattern, the PFC@PLGA-Pluronic F68 group showed a slower initial growth, with a more significant increase only appearing in the later stages of storage, suggesting that the introduction of Pluronic F68 effectively delayed the system's instability process. This may be because Pluronic F68, as a nonionic surfactant, can form a steric hindrance layer composed of hydrophilic segments on the particle surface, thereby reducing direct contact and the probability of aggregation between particles; simultaneously, the PLGA coating layer also provides a certain degree of interfacial protection for the PFC droplets. Therefore, the PFC@PLGA-Pluronic F68 composite system can maintain a small particle size and good dispersion for a relatively long period. In contrast, the PFC group lacks a stable coating structure and is prone to droplet fusion during storage; while the PFC@PLGA group, although possessing a polymer coating layer, still exhibits significant aggregation under long-term storage due to the lack of an outer hydrophilic stable canopy.

[0105] Figure 12Figure b further illustrates the changes in PDI of the three sample groups during storage. Overall, the PDI of all samples gradually increased with time, indicating that the particle size distribution gradually widened with increasing storage time, leading to a decrease in system homogeneity. Among them, the PDI of the PFC@PLGA group increased the fastest, from approximately 0.22 initially to approximately 0.52 on day 5, suggesting that its particle distribution widened rapidly in a short period, resulting in poor system dispersion stability. The PDI of the PFC group increased from approximately 0.18 to approximately 0.39 on day 6. Although its increase was lower than that of the PFC@PLGA group, it still showed a clear trend of deteriorating distribution. In contrast, the PFC@PLGA-Pluronic F68 group maintained a low PDI level throughout the early stages, with an initial value of approximately 0.12. It only increased to approximately 0.21 on day 6, and although it continued to increase slowly thereafter, reaching approximately 0.48 on day 12, the overall change was more gradual, indicating better particle size uniformity and dispersion stability in the early stages of storage.

[0106] The results, combining particle size and PDI, show that the PFC@PLGA-Pluronic F68 composite nanoemulsion exhibits the best overall stability among the three samples. Although the particle size and PDI inevitably increase with prolonged storage time, the growth rate is significantly slower and the stability is maintained for a longer period compared to the PFC and PFC@PLGA systems. This indicates that Pluronic F68 modification plays an important role in improving particle interface properties, reducing droplet coalescence, and delaying system instability. The aforementioned Zeta potential results show that the introduction of Pluronic F68 reduces the absolute value of the particle surface potential, suggesting that its stabilization mechanism is not solely dependent on electrostatic repulsion, but more likely originates from the steric hindrance effect of the formation of hydrophilic segments on the surface. Combining the shell-like structure observed by TEM and the component coexistence characteristics confirmed by ATR-FTIR, it can be concluded that the PFC@PLGA-Pluronic F68 composite nanoemulsion has successfully formed a stable structure with interfacial coating characteristics, thereby significantly improving the storage stability of the perfluorocarbon system.

[0107] Test Example 7 This test case explores the changes in the system state of different systems during electrochemical reactions. Figure 13Figure a further illustrates the variation of acetic acid concentration in different systems. Overall, the acetic acid concentration in all three groups increased over time, but the rate of increase and final yield differed significantly. In the PFC-Pluronic F68 group, the acetic acid concentration increased from approximately 2.6 mmol / L to approximately 10.7 mmol / L in the first 5 days, then stabilized at around 11.6 mmol / L, indicating that this system had a certain acetic acid-promoting effect in the initial stage, but the subsequent promoting effect was limited. The PFC@PLGA group showed a faster acetic acid accumulation rate in the early stage of the reaction, reaching approximately 14.9 mmol / L on day 3 and close to 19.4 mmol / L on day 5, after which it remained relatively stable, indicating that PLGA coating can improve the dispersibility and mass transfer efficiency of perfluorinated carbon in the system to some extent, thereby enhancing acetic acid production. However, the PFC@PLGA-Pluronic F68 group exhibited the most significant advantage, with its acetic acid concentration continuously increasing throughout the reaction cycle, rising from approximately 3.8 mmol / L on day 1 to approximately 39.1 mmol / L on day 14, without a noticeable plateau, significantly higher than the other two groups. These results indicate that the composite nanoemulsion possesses superior sustained substrate supply capacity and long-term stability during the electrochemical reaction, enabling it to promote the conversion of electrons and carbon sources into the target product, acetic acid, by microorganisms for a longer period.

[0108] Figure 13 Figure b shows the Faraday efficiency results, further reflecting the differences in electron utilization efficiency among different systems. The PFC-Pluronic F68 group had a Faraday efficiency of approximately 41.6% on day 1, which increased slightly on day 2 but then rapidly declined, reaching only about 15.9% by day 6, indicating that this system is difficult to maintain the directional electron conversion to acetic acid in the long term. The PFC@PLGA group exhibited higher Faraday efficiency in the early stages, approximately 62.6% on day 1 and remaining around 61% on day 3, but then declined significantly from day 4, dropping to about 17.4% on day 5, indicating that its promoting effect on electron utilization efficiency was mainly concentrated in the early stages of the reaction. In contrast, the PFC@PLGA-Pluronic F68 group showed stronger maintenance ability throughout the entire cycle, with its Faraday efficiency consistently remaining around 50% or higher for the first 7 days. Although it gradually declined thereafter, it still remained above 30% by day 10, and was approximately 11.3% on day 14. Although it also decayed later, the overall rate of decline was significantly slower than the other two groups, indicating that the composite system can maintain a high electron conversion efficiency for a longer period of time, allowing more electrons to be used for the generation of the target product, acetic acid.

[0109] The results of tests 6 and 7 show that the PFC@PLGA-Pluronic F68 group exhibits the best overall performance in the electrochemical reaction system. On the one hand, this system maintains a stable pH environment and a high and stable OD throughout the entire reaction cycle. 545 nm This indicates that it provides excellent support for the system's operational stability and microbial activity. Furthermore, its acetic acid production is significantly higher than that of the PFC-Pluronic F68 and PFC@PLGA groups, and it maintains a high Faraday efficiency for a longer period. This suggests that the composite nanoemulsion not only improves the stable state of perfluorinated carbon in the reaction system but also enhances mass transfer and electron utilization efficiency. Combining the aforementioned particle size, PDI, Zeta potential, and ATR-FTIR analyses, it is evident that PLGA coating provides basic interfacial protection for PFC, while further modification of Pluronic F68 effectively reduces the risk of particle aggregation and instability by forming a hydrophilic outer layer and a sterically stable structure, enabling the composite nanoemulsion to function more sustainably in the electrochemical environment. Therefore, the PFC@PLGA-Pluronic F68 composite nanoemulsion has significant advantages in enhancing the electrochemical acetic acid production process and can serve as an important functional material for constructing efficient gas transport and electron utilization systems.

[0110] In summary, the PFC-Pluronic F68 system exhibits a short-lasting reaction-promoting effect due to the lack of a stable polymer coating structure; while the PFC@PLGA system significantly improves acetic acid production and Faradaic efficiency in the initial stages of the reaction, its performance declines rapidly in the later stages; whereas the PFC@PLGA-Pluronic F68 system combines good environmental stability, sustained acetic acid accumulation capacity, and high electron utilization efficiency, demonstrating the best long-term operating performance. This indicates that constructing a composite structure of a PLGA coating layer and a Pluronic F68 hydrophilic interface layer on the surface of PFC emulsions is an effective strategy to improve the stability of perfluorocarbon electrochemical applications and the ability to promote acetic acid production.

[0111] In summary, the perfluorinated carbon nanoemulsion hydrogen carrier of the present invention is used for efficient dissolution and transport of H2 to alleviate the limitation of H2 mass transfer, continuously provide reducing power for the microbial electrosynthesis process, and improve the yield, efficiency and stability of acetic acid production without affecting microbial activity.

[0112] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for preparing a perfluorinated carbon nanoemulsion hydrogen carrier, characterized in that, The preparation method includes: (1) Dissolve the polylactic acid-glycolic acid copolymer in a solvent, add perfluorinated carbon, then add polyvinyl alcohol solution and mix, and then perform ultrasonic treatment; The perfluorocarbons include perfluorohexane and perfluoronaphthane; (2) Add polyvinyl alcohol solution to the solution after ultrasonic treatment in step (1), stir, centrifuge and wash to obtain nanoparticles; (3) The nanoparticles obtained in step (2) are dispersed in deionized water, and a surfactant is added and stirred to obtain the nanoparticles.

2. The method for preparing a perfluorinated carbon nanoemulsion hydrogen carrier according to claim 1, characterized in that, In step (1), the ratio of polylactic acid-glycolic acid copolymer to perfluorinated carbon is (10-15) mg: 100 μL; Preferably, in step (1), the volume ratio of perfluorohexane to perfluoronaphthalene is 1:(0.5-2); Preferably, in step (1), the solvent includes any one or a combination of at least two of dichloromethane, chloroform, ethyl acetate, or acetone; Preferably, in step (1), the amount of solvent added is 1-4 mL.

3. The method for preparing a perfluorinated carbon nanoemulsion hydrogen carrier according to claim 1 or 2, characterized in that, In step (1), the amount of polyvinyl alcohol solution added is 0.5-3 mL; Preferably, in step (1), the concentration of the polyvinyl alcohol solution is 3-8%; Preferably, in step (1), the ultrasonic treatment time is 3-8 min, and the ultrasonic treatment procedure is 1-5 s ultrasonic treatment and 5-10 s treatment shutdown.

4. The method for preparing a perfluorinated carbon nanoemulsion hydrogen carrier according to any one of claims 1-3, characterized in that, In step (2), the concentration of the polyvinyl alcohol solution is 3-8%; Preferably, in step (2), the amount of polyvinyl alcohol solution added is 10-15 mL; Preferably, in step (2), the stirring time is 12-36 h; Preferably, in step (2), the centrifugation process is carried out at a temperature of 0-4°C, a centrifugation speed of 8000-12000 rpm, and a time of 5-15 min.

5. The method for preparing a perfluorinated carbon nanoemulsion hydrogen carrier according to any one of claims 1-4, characterized in that, In step (3), the surfactant includes Pluronic F68; Preferably, in step (3), the final concentration of the surfactant is 0.5-3%; Preferably, in step (3), the stirring temperature is 0-4℃ and the stirring time is 12-36 h.

6. The perfluorinated carbon nanoemulsion hydrogen carrier prepared by the method described in any one of claims 1-5.

7. A method for the electrochemical reduction of carbon dioxide based on microorganisms, characterized in that, The method includes: S.ovata The bacterial culture was mixed with the perfluorinated carbon nanoemulsion hydrogen carrier described in claim 6 and then subjected to microbial electrochemical culture.

8. The method for microbial electrochemical reduction of carbon dioxide according to claim 7, characterized in that, The method includes: (a) In constant potential mode, reduction is carried out using an electrochemical workstation with a three-electrode system. The cathode chamber and the anode chamber are separated by an anion exchange membrane. A mixed gas is introduced into the cathode chamber and a reducing solution is added to remove oxygen. (b) After deoxygenation in step (a), an injection is made into the cathode chamber. S.ovata The bacterial culture was carried out using a perfluorinated carbon nanoemulsion hydrogen carrier.

9. The method for microbial electrochemical reduction of carbon dioxide according to claim 8, characterized in that, In step (a), the mixed gas comprises 15-25% CO2 and 75-85% N2; Preferably, in step (a), the ventilation time of the mixed gas is 12-36 h, and the flow rate is 1-3 mL / min; Preferably, in step (a), the reducing solution comprises 0.5-3 g / L sodium sulfide nonahydrate and 40-60 mM phosphate buffer; Preferably, in step (a), the amount of the reducing solution added is 0.1-1 mL.

10. The method for microbial electrochemical reduction of carbon dioxide according to claim 8 or 9, characterized in that, In step (b), the S.ovata The amount of bacterial solution added is 1-10 mL; Preferably, in step (b), the S.ovata OD of bacterial culture 545nm It is 0.3-0.8; Preferably, in step (b), the amount of the perfluorinated carbon nanoemulsion hydrogen carrier added is 1-8 mL; Preferably, the method further includes hydrogen perfuming the perfluorinated carbon nanoemulsion hydrogen carrier before use; Preferably, the hydrogen flow rate for the hydrogen treatment is 1-10 mL / min; Preferably, the hydrogen permeation treatment time is 3-5 minutes.